Vocal Cysts: Clinical, Endoscopic, and Surgical Aspects - Garcia Martins, Regina Helena [UNESP]; Santana, Marcela Ferreira; Mendes Tavares, Elaine Lara (Mosby-elsevier, 2011)
Vocal cysts are benign laryngeal lesions, which affect children and adults. They can be classified as epidermic or mucous-retention cyst.Objective. The objective was to study the clinical, endoscopic, and surgical aspects of vocal cysts.Methods. We reviewed the medical charts of 72 patients with vocal cysts, considering age, gender, occupation, time of vocal symptoms, nasosinusal and gastroesophageal symptoms, vocal abuse, tabagism, alcoholism, associated lesions, treatment, and histological details.Results. of the 72 cases, 46 were adults (36 females and 10 male) and 26 were children (eight girls and 18 boys). As far as occupation is concerned, there was a higher incidence of students and teachers. All the patients had symptoms of chronic hoarseness. Nasosinusal (27.77%) and gastroesophageal (32%) symptoms were not relevant. Vocal abuse was reported by 45.83%, smoking by 18%, and alcoholism by 8.4% of the patients. Unilateral cysts were seen in 93% of the cases, 22 patients had associated lesions, such as bridge, sulcus vocalis, and microweb. Surgical treatment was performed in 46 cases. Histological analysis of the epidermic cysts revealed a cavity with caseous content, covered by stratified squamous epithelium, often keratinized. Mucous cysts presented mucous content, and the walls were coated by a cylindrical ciliated epithelium.Conclusion. Vocal cysts are benign vocal fold lesions that affect children and adults, being often associated with vocal overuse, which frequently affects people who use their voices professionally. Vocal symptoms are chronic in course, often times since childhood, and the treatment of choice is surgical removal. A careful examination of the vocal folds is necessary during surgery, because other laryngeal lesions may be associated with vocal cysts.
Keywords: Vocal cyst; Voice; Videolaryngostroboscopy